Cytotoxic terpenoids from the stem bark of Taxus wallichiana. (December 2022) - Ngoc, Ninh Thi; Cuong, Dang Viet; Hanh, Tran Thi Hong; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Ha, Chu Hoang; Quang, Tran Hong
Abstract: Chemical study of the stem bark of Taxus wallichiana Zucc. afforded the isolation of two new cyclopenta[ b ]naphthalene terpenoids, wallichianones A (1 ) and B (2 ) and 13 taxane diterpenoids, baccatin III (3 ), 10-deacetylbaccatin III (4 ), baccatin IV (5 ), 1-dehydroxybaccatin IV (6 ), 1-deoxybaccatin VI (7 ), taxol (8 ), 10-deacetyltaxol (9 ), 7- epi -10-deacetyltaxol (10 ), taxol-7-xyloside (11 ), 7-xylosyl-10-deacetyltaxol C (12 ), cephalomannine (13 ), 10-deacetylcaphalomannine (14 ), and 7- epi -10-deacetylcephalomannine (15 ). Their structures were identified by comprehensive analyses of the spectroscopic methods, including NMR and mass spectra. The absolute configurations of 1 and 2 were clarified by time-dependent density functional theory (TD-DFT) electronic circular dichroism (ECD) spectroscopic analyses. Compounds 3 and 7–15 showed cytotoxicity against all five human cancer cell lines, including lung (SK-LU-1), liver (HepG2), breast (MCF7), skin (SK-Mel-2), and prostate (LNCaP), with IC50 values ranging from 1.4 ± 0.2 to 88.1 ± 5.8 μM. Compounds 9–11, 14, and 15 were additionally cytotoxic against human embryonic kidney (HEK-293A) cell line (IC50 = 14.5 ± 1.0–48.4 ± 1.0 μM), however, 13 was noncytotoxic toward this cell line. The positive control, ellipticine showed cytotoxicity against all the cell lines, with IC50 values in a range of 1.5 ± 0.1–2.0 ± 0.3 μM. Preliminary analysis of the structural and cytotoxicity relationship of compounds 3–15 suggested that the phenylalanine substituent at C-13 may contribute an important role for the cytotoxicity of the taxane diterpenoids. Graphical Abstract: ga1 Highlights: 15 compounds were isolated from Taxus wallichiana stem bark. 2 new and 13 known compounds were identified by spectroscopic analyses. Cytotoxicity on SK-LU-1, HepG2, MCF7, SK-Mel-2, LNCaP, HEK-293A cell lines.